The Degree of Inflammation and Length of Hospital Stay in Acute Exacerbation of COPD Patients After Secretome Administration - Hendrastutik Apriningsih; Yusup Subagio Sutanto; Reviono Reviono; Artrien Adhiputri; Windu Prasetya; Fahlevie Fahlevie; Fitrotin Aziza (Jurnal Respirologi Indonesia, 2023)
Background: Acute exacerbation of COPD (AECOPD) is a decrease in respiratory conditions compared with regular conditions that require additional treatment, increase risk of hospitalization or demand intensive care unit. The neutrophil-to-lymphocyte ratio (NLR) describes the balance between the severity of inflammation and the immune system and is considered as an important systemic inflammatory marker. Length of hospital stay (LHS) is important in predicting the severity of AECOPD, in which longer LHS indicates greater severity of AECOPD. Secretome has been shown to have the ability to exert immunomodulatory effects, reduce lung injury and inflammation in several models of lung inflammation and immune-mediated lung disease. This study aimed to assess the differences between NLR and LHS in AECOPD patients who received a secretome and those who did not.Methods: This study involved 30 AECOPD patients whom assigned into two groups. Secretome and standard therapy were administered in the treatment group, whilst the control group only received the standard therapy. Statistical analysis used different test, the unpaired group difference test using Mann Whitney and the independent test, the paired group difference test using Wilcoxon rank test and Pair test. Result is significant if the P<0.05.Results: NLR value in the treatment group experienced a lower increase than the control group, yet statistically insignificant (P=0,187). Secretome decreased the LHS in AECOPD patients, and statistically significant with (P=0,028). Conclusion: Administration of secretome led to a lower increase in NLR value and decreased LHS AECOPD patients.